Enhancing root physiology for increased yield in water-saving and drought-resistance rice with optimal irrigation and nitrogen - Hou, Danping; Liu, Kun; Liu, Shikun; Li, Juncai; Tan, Jinsong; Bi, Qingyu; Zhang, Anning; Yu, Xinqiao; Bi, Junguo; Luo, Lijun (Frontiers in Plant Science, 2024)
[Objectives] Water-saving and drought-resistance rice (WDR) plays a vital role in sustainable development of agriculture. Nevertheless, the impacts and processes of water and nitrogen on grain yield in WDR remain unclear. [Methods] In this study, Hanyou 73 (WDR) and Hyou 518 (rice) were used as materials. Three kinds of nitrogen fertilizer application rate (NFAR) were set in pot experiment, including no NFAR (nitrogen as urea applied at 0 g pot−1), medium NFAR (nitrogen as urea applied at 15.6 g pot−1), and high NFAR (nitrogen as urea applied at 31.2 g pot−1). Two irrigation regimes, continuous flooding cultivation and water stress, were set under each NFAR. The relationships between root and shoot morphophysiology and grain yield in WDR were explored. [Results] The results demonstrated: 1) Under the same irrigation regime, the grain yield of two varieties increased with the increase of NFAR. Under the same NFAR, the reduction of irrigation amount significantly reduced the grain yield in Hyou 518 (7.1–15.1%), but had no substantial influence on the grain yield in Hanyou 73. 2) Under the same irrigation regime, increasing the NFAR could improve the root morphophysiology (root dry weight, root oxidation activity, root bleeding rate, root total absorbing surface area, root active absorbing surface area, and zeatin + zeatin riboside contents in roots), and aboveground physiological indexes (leaf photosynthetic rate, non-structural carbohydrate accumulation in stems, and nitrate reductase activity in leaves), in two varieties. Under the same NFAR, increasing the irrigation amount could significantly increase the above indexes in Hyou 518 (except root dry weight), but has little effects on Hanyou 73. 3) Analysis of correlations revealed that the grain yield of Hyou 518 and Hanyou 73 were basically positively correlated with aboveground physiology and rootmorphophysiology, respectively. [Conclusions] The grain yield could be maintained by water stress under medium NFAR in WDR. The improvement of root morphphysiology is a major factor for high yield under irrigation regime and NFAR treatments in WDR. Keywords: Water-saving and drought-resistance rice; Irrigation regime; Nitrogen fertilizer application rate; Grain yield; Root morphology and physiology